UEFA and the European Union: From Confrontation to Co-operation? - Borja García (Journal of Contemporary European Research, 2007)
This article investigates the relationship between UEFA, as European football’s governing body, and the EU. It assesses the evolution of UEFA as a football governing body since the Bosman ruling (1995) until current initiatives such as the rules on locally-trained players (2005-2006). The paper traces the evolution of UEFA’s reactions to the increasing involvement of EU institutions in football matters, with special focus on the regulation of the players’ market. It is argued that UEFA’s attitude towards the EU has changed in the last ten years. Whilst the EU was seen as a threat for UEFA in 1995, it is now considered a ‘long term strategic partner’. Two main reasons can be identified for UEFA’s evolution. First and foremost, UEFA has been forced to accept the primacy of European law and its application to the activities of football organisations. UEFA has had no option but to adapt to the impact of European law and policies on its activities. This has lead to a relationship of ‘supervised’ autonomy between UEFA and the EU institutions. Second, UEFA’s strategic vision to preserve its own position within the governance structures of football. UEFA has tried to enhance its legitimacy within football’s governing structures by engaging in policy co-operation with EU authorities. This paper draws almost entirely on empirical research conducted through elite interviews and the review of official documents.